(untitled) (Biological Sciences - PJSIR, 2006)
The solvent extraction and separation of Al(III) and Ni(II) from aqueous medium using Cyanex-272 [bis- (2,4,4-trimethylpentyl) phosphinic acid] in kerosene has been investigated as functions of contact time, aqueous phase acidity (pH), concentration of extractant in the organic phase, temperature, and loading capacity of the extractant. The equilibrium was reached within 9 min for Al(III) and 2 min for Ni(II). It was observed that the amount of Al(III) extraction was about 65% with 0.1 mol/l Cyanex-272 in kerosene at (26 ± 1) °C and pH 4.2, whereas at the same time the amount of Ni(II) extraction was about 8.5% with the same condition. In both cases, the metal ion [Al(III) and Ni(II)] concentration in the organic phase gradually increased with the time of extraction until the curves levelled off. The extraction of Al(III) increasesed with increasing concentration of the extractant, aqueous phase acidity (pH), and the temperature. However, the amount of Ni(II) extraction at all temperatures was negligible and decreased with increasing extractant concentration. The temperature dependence data gave ÄH = 15.23 kJ/mol up to 60 °C, suggesting endother- mic extraction. The loading capacity of Al(III) and Ni(II) was about 25.75 g and 0.5 g, respectively per mole of Cyanex- 272, with 0.2 M Cyanex-272 at pH 4.1. Loading data indicates Al : Cyanex-272 ratio varied from 0.95 : 1 to 1.6 : 1 for Al(III) extraction indicating almost 1 : 1 complex formation in the organic phase.